Learning Support for Pre-University Students: Comparison of Gender and Class Streams - Baskaran, Kasturi; Salleh, Umi Kalsum Mohd; Tembe, Hutkemri (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to examine the learning support for pre-university students in managing their Pengajian Am course works in the state of Perak. Learning support in the context of this study refers to support from parents, teachers, peers and the school environment in assisting pre-university students to complete their course works. This study involves 425 pre-university students. Semester 2 students were randomly selected from different backgrounds including different gender and class streams. Research data were collected through questionnaires and then analysed using the Statistical Package for Social Science software version 25.0. Findings show a high level of learning support received by pre-university students in Perak. In addition, significant differences were observed in learning support among pre-university students on the basis of gender and class streams. Results are intended to serve as a guide for parents, teachers, peers and school in enhancing learning support to assist pre-university students in completing their coursework and can serve as a route for future studies.